The Influential Factors of Children to Work - Ikawati, Ikawati (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research is to analysis the influential factors children to work and its impact on their physical, psychical, and social condition, and its contribution on economic and social, including family, community, and government efforts on stemming the number of working children. This research is qualitative descriptive, research location determined purposively in West Java, East Java, West Nusa Tenggara. Research subjects are children working abroad that happen having vacation in their villages. Based on purposive determination, it is found 30 children as samples. Data gathered through interview, focus group discussion, observation, and documentary analysis. Data are analyzed through qualitative-descriptive technique. The research finds that the causal factors of children to work are the condition of parent education and their low income, and the number of many family members that should be held, and family in harmony. The impact of children working is delaying their growth, physically, psychologically, and socially. The contribution of children work is increasing the social and economy of the family, such as income and schooling members of the family, and increasing members of the family in social activity. Some family, community, and government efforts to stem the number of working children are sending the children until primary school, diffusing information on the important of children education, monitoring on learning time, forming learning group, looking for reference on school grant, making data on children drop out, giving work skills, giving entrepreneur capital for family with vulnerable economy, monitoring on identity card faking, and limiting working letter to children under age. Some of the government effort to stem the number of working children are, nine-year schooling obligation program, electronic identification card, issuing regulation on the protection of working children and law measurement on children traffickers. It is recommended for the Ministry of Social Affairs through the Directorate of Violent Victims of Migrant Workers on poor family empowerment program, that in sending migrants workers areas based on local potential, children committing in work should be prevented.